Perinatal taurine exerts a hypotensive effect in male spontaneously hypertensive rats and down-regulates endothelial oxide nitric synthase in the aortic arch - Mensegue, Melisa F. (2020)
Essential hypertension is considered to be a result of the interaction between genetic and environmental factors, including perinatal factors. Different advantageous perinatal factors proved to have beneficial long-lasting effects against an abnormal genetic background. Taurine is a ubiquitous sulphur-containing amino acid present in foods such as seafood. The antihypertensive effects of taurine have been reported in experimental studies and in human hypertension. We aimed to investigate the effects of perinatal treatment with taurine in spontaneously hypertensive rats (SHR), a known model of genetic hypertension. Female SHR were administered with taurine (3 g/L) during gestation and lactation (SHR-TAU). Untreated SHR and Wistar-Kyoto rats (WKY) were used as controls. Long-lasting effects in offspring were investigated. Addition of taurine to the mother's drinking water reduced blood pressure in adult offspring. No differences were observed in cardiac hypertrophy. Findings on morphometric evaluations suggest that perinatal treatment with taurine would be partially effective in improving structural alterations of the aorta. Modifications in gene expression of Bcl-2 family members and upregulation of endothelial nitric oxide synthase in the aorta of 22-week-old male offspring were found. No differences were observed on relative telomere length in different cardiovascular tissues between SHR and SHR-TAU. Altogether results suggest that taurine programming, albeit sex specific, is associated with gene expression changes which ultimately may lead to improvement of aortic remodelling and enhanced endothelial function because of augmented nitric oxide (NO) production.